Control of general and special physical preparedness by qualified handballers - Tyshchenko, V.; Popovich, O. (Journal of Physical Education and Sport, 2015)
The features of control of general and special physical preparedness by qualified handballers. The necessity to use facilities during workout sessions in professional sports and particularly in handball has been ascertained. Novel informative testing techniques using flashlight tests have been discussed. Application of test exercises, aimed at evaluation of psychomotor system by qualified handball players of the Ukrainian Super League, has been analyzed.